2016
DOI: 10.1002/jmri.25290
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between malignant and benign thyroid nodules and stratification of papillary thyroid cancer with aggressive histological features: Whole-lesion diffusion-weighted imaging histogram analysis

Abstract: Whole-lesion ADC histogram analysis might help to differentiate malignant nodules from benign ones and show the PTCs with extrathyroidal extension. J. Magn. Reson. Imaging 2016;44:1546-1555.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 38 publications
(53 reference statements)
3
39
0
Order By: Relevance
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
“…45 However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments. [9][10][11]14,[16][17][18][19][20][21][32][33][34] Thus, the best method of ADC measurement for clinical application in DW-MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies. Lastly, in our study the CoV, which represents the ratio of the standard deviation to the mean, could be higher in MSR and OSR methods compared to the other measurement protocols because of the lower mean ADC value of the MSR and OSR methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of the authors’ knowledge, only one study used ADC histogram analysis in thyroid cancer to differentiate benign from malignant nodules and furthermore reveal extra-thyroidal growth of papillary thyroid cancer [18]. So far, no studies demonstrated predictability of lymph node involvement by ADC histogram analysis of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%